IMPROVING STUDENTS’ READING SKILLS THROUGH CONTEXT CLUES AND PUNCTUATIONS AT GRADE XII MS 4 OF SMA NEGERI PLUS OF RIAU PROVINCE - Tengku Emadesti (English Study Program University of Pasir Pengaraian, 2017)
This article reports on a study intended to explain whether context clues and punctuations could better improve the students‟ reading skills at grade XII MS 4 of SMA Negeri Plus of Riau Province and to explain what factors that change it. This research was conducted through a classroom action research at SMA Negeri Plus of Riau Province, in 2017/2018 academic year. This classroom action research consisted of two cycles constituting 3 meetings for each cycle. Participants of the research were 25 of students of the grade XII MS 4 of SMA Negeri Plus Riau Province.The data were collected by using observation checklists, field notes, and test. Qualitative data were analyzed by data managing, reading or memoing, describing, classifying, interpreting. Quantitative data were analyzed by percentage (score of reading skills), Matrix and graph.The result of this research shows that the students‟ reading skills increased in each cycles. In the first cycle, the percentage of students‟ reading skills was 80.60%. But, the result was unsatisfactory yet. In the second cycle, the increase of students‟ reading skills was 90.08%. It means that there is an increase of students‟ reading skills in second cycles. In conclusion, the teaching of context clues and punctuations skills could increase the students‟ reading skills in understanding reading text. There were some factors that influence the changing of the students‟ reading skills by implementing context clues and punctuations, namely;(a) Time allocation in implementing of the context clues and punctuations.(b) Students‟ understanding in implementing the context clues and punctuations in reading skills. (c) Classroom atmosphere while the context clues and punctuations were implemented.